SOCIAL MEDIA USE, KNOWLEDGE, AND ATTITUDES TOWARDS PEOPLE LIVING WITH HIV/AIDS AMONG HIGH SCHOOL STUDENTS IN AN INDONESIAN TOURISM REGION - Dana NINDREA, Ricvan; DARMA , Ika Yulia; SUKMA , Muthia; MARDIAH, Aini; AGUSTIAN , Dede Rahman; SHOLIHATI , Mursyidah (African Journal of Infectious Diseases (AJID), 2024)
Background: Social media has become an integral part of adolescent life in Indonesia, particularly in tourism regions. It serves as a platform for disseminating information, including about HIV/AIDS. However, it also has the potential to spread misinformation and harmful content, which can increase stigma and discrimination against people living with HIV/AIDS (PLWHA). Aim: The aim of this study was to determine the relationships between social media use, knowledge, and attitudes towards PLWHA among high school students in an Indonesian tourism region. Methods: This research utilized a school-based cross-sectional study design in several high schools located in Bukittinggi City, a renowned tourist destination in West Sumatra Province, Indonesia. The study sample comprised high school students aged 15-18 years, with a total of 118 respondents selected. The sample was chosen using a multistage stratified clustered sampling method. The variables measured in this study included social media usage, HIV/AIDS knowledge, and attitudes towards PLWHA. To test the research hypotheses, data analysis was conducted using structural equation modeling techniques. P<0.05 is considered significant. Results: There were relationships between social media use and knowledge of HIV/AIDS (β=0.614, t-value=9.327, p-value=<0.001), knowledge of HIV/AIDS and attitudes towards PLWHA (β=0.601, t-value=8.344, p-value=0.014) and social media use and attitudes towards PLWHA (β=0.218, t-value=2.469, p-value=<0.001). Conclusion: This study confirmed significant relationships were found between social media use, knowledge, and attitudes towards PLWHA. The results highlight the necessity for comprehensive interventions and ongoing support to promote the well-being of students amid the dynamic changes in global tourism.